A slippery reality: the epistemological shifting sands of tokogeny, phylogeny, lineages and species delimitation. Issue 7 (3rd October 2021) - Brower, Andrew V. Z.
Abstract : This essay provides an alternative perspective on the history of classification, species and subspecies concepts to that presented in a recent review by Padial and de la Riva. Central points of difference relate to Darwin's role in revolutionizing classification, Willi Hennig's role in the development of the phylogenetic species concept, the metaphysics and epistemology of species as lineage segments, the true history of the subspecies concept, and the impact of large amounts of genetic data on the accuracy and precision of species/subspecies delimitation. Possession of a clear understanding of the history of systematics, and a chronology of which ideas inform which other ideas, provides critical background knowledge to build a sound conceptual framework for interpreting the nuances of phylogenetic evidence today. A glossary of potentially unfamiliar terms is included as an appendix.